What happened to savings during the financial crisis: a dynamic panel analysis of Asian-5 countries. - Thanoon, Marwan Abdul-Malik; Baharumshah, Ahmad Zubaidi (Springer, 2007)
This article examines the determinants of saving rates in five Asian (Asian-5; Malaysia, Singapore, Thailand South Korea and the Philippines) countries over the 1970-2000 period. The focus is on the relationship between savings rates and foreign capital inflows before and in the financial crises. Major findings from the dynamic panel regressions are: (i) foreign savings depresses domestic savings ratio in the short as well as in the long run and the offset appears to be larger in the crisis period; (ii) real interest has a small negative effect on savings in the short and long run; (iii) the demographic factor explains a large portion of the long run trends but not the short-term fluctuations in savings rates; and (iv) high savings ratios in the countries studied is linked to the export sector. © Springer Science+Business Media, LLC 2006.